4CPS-052 Evaluation of piperacillin/tazobactam dosage in septic patients attending the emergency department. (24th March 2020) - Ruiz, J; Juanes Borrego, A; López Vinardell, L; Plaza Diaz, A; Mangues Bafalluy, MA; Puig Campmany, M
Abstract : Background and importance: Although there is consensus for beta-lactam administration for extended infusions in critical care units, the use of this strategy in emergency departments remains unclear. Aim and objectives: To evaluate the probability of achieving an adequate pharmacokinetic/pharmacodynamic ratio for different dosages of piperacillin/tazobactam in septic patients attending an emergency department. Material and methods: A simulation study was carried out based on gram negative bacterial strains causing bacteraemia in septic patients treated in an emergency department (July 2018–December 2019). Two doses were evaluated, 4/0.5 g every 6 hours or 8 hours given as 0.5 hour or 3 hour infusion, in three different renal clearance rates (<30, 70 and 120 mL/min). Pharmacokinetic parameters were obtained from the literature. Minimum inhibitory concentration (MIC) values to piperacillin/tazobactam were obtained from Spanish records (trial database, TEST). Time above MIC was obtained according to the following equation: fT >MIC=[(t2−tinf)−t1] × (100/τ), where t1 was the time at which the free serum concentration reached the MIC, t2 the post-infusion time at which the free serum concentration equalled the MIC in the elimination phase and τ the dosing interval. A 1000 subject Monte Carlo simulation was performed using Microsoft Excel per dosing and rate of renal function. Results: Sixty patients with gram negative bacteraemia were included. The predominant species were Escherichia coli (34, 56.7%), Klebsiella pneumoniae (14, 23.3%) and Pseudomonas aerugino sa (6, 10%). The probability of target attainment (PTA) fT >100% MIC for piperacillin 4 g/8 hour dose was 60.3% and 81.8% for the 0.5 hour and 3 hour infusions for a ClCr >120 mL/min and 75.1% and 94.3% for a ClCr=70 mL/min. For the 4 g/6 hour dose, the PTA fT >100% MIC was >90% for both infusions at 0.5 and 3 hours. For tazobactam, the PTA fT >70% MIC for a ClCr=70 mL/min for the doses 0.5 g/8 hours and 0.5 g/6 hours were 56% and 89%, increasing in the extended infusion of 3 hours (87% and 98%). For a ClCr >120 mL/min, this probability was significantly reduced, being <50% for the dose 0.5 g/8 hours in a 0.5 hour infusion. Conclusion and relevance: The pharmacokinetic/pharmacodynamic objective of fT >100% MIC for piperacillin/tazobactam required a dose of 4/0.5 g/6 hours or extended infusion, especially in patients with high renal clearance and in strains with high levels of expression of beta-lactamases. References and/or acknowledgements: No conflict of interest.